(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This study explores the development of critical thinking skills among fourth-grade students within the Lithuanian curriculum, where students are expected not only to perform calculations but also to formulate hypotheses, justify solutions, and explore alternative problem-solving methods (Mathematics General Curriculum, 2022). Despite curricular ambitions, many teachers lack clear strategies for fostering these skills in practice. To address this, a qualitative study using semi-structured interviews with six primary school mathematics teachers was conducted. The interviews were transcribed and analysed through content analysis to uncover common methods and challenges. Findings revealed that teachers encourage critical thinking through interactive tasks, real-life problem analysis, mathematical storytelling, project work, group discussions, and the use of digital applications. Key activities supporting critical reasoning include problem-solving tasks, mathematical modelling, reflective exercises, and structured classroom discussions. However, the study identified a persistent difficulty among teachers in selecting and designing tasks that effectively stimulate analytical thinking. As a result, the research recommends implementing more structured, student-cantered strategies and collaborative learning to better cultivate critical thinking. Furthermore, the integration of inquiry-based learning and digital technologies is emphasized as promising in enhancing students’ analytical and problem-solving abilities. The insights gained from this study provide valuable guidance for teachers seeking to align instructional practices with curriculum expectations and promote deeper mathematical reasoning from an early age.